Two new genera for the Botyodes species complex (Lepidoptera: Pyraloidea: Crambidae) - Singh, Navneet; Kirti, Jagbir Singh; Singh, Harsimran; Ranjan, Rahul (Zootaxa, 2019)
Two new genera of Spilomelinae, Neobotyodes Singh, Kirti & Singh, gen. nov. (Type species: Botyodes crocopteralis Hampson, 1898) and Caldubotys Singh, Kirti & Singh, gen. nov. (Type species: Botys caldusalis Walker, 1859) are established. Morphological descriptions and diagnoses are provided for both the new genera. Two new combinations Neobotyodes crocopteralis and Caldubotys caldusalis are also established.